Analisis Dampak Perhitungan Aset Tetap Berdasarkan Jenis Kelompok, Masa Manfaat, Tarif Penyusutan Berdasarkan Undang – Undang Perpajakan Pasal 11 Pph No. 36 Tahun 2008 Terhadap Laba Rugi PT Wahana Kreasi Nusantara Tahun 2013 - 2018 - Diana Gustinya, SE., M.Ak. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
To find out the calculation of fixed assets based on the type of group, useful life, depreciation rates of the Taxation Act (article 11 of the Income Tax Law No. 36 of 2008) at PT Wahana Kreasi Nusantara. And the impact of applying the difference in the calculation of depreciation of fixed assets on the income statement of PT Wahana Kreasi Nusantara from 2013 to 2018. This study uses a descriptive qualitative method with secondary data used in this study is the data of fixed assets and income statements of PT Wahana Kreasi Nusantara from 2013 to 2018. PT Wahana Kreasi Nusantara uses the straight-line method in calculating all its fixed assets, but in determining the type of group, the useful life and depreciation rates determined by the company are not in accordance with the Taxation Law Regulation (article 11 of Income Tax Law No. 36 years 2008). So that the incompatibility of types of groups, the useful life and depreciation rates between companies with the Taxation Law Regulation (article 11 of the Income Tax Law No. 36 of 2008) results in the difference in depreciation costs incurred by the company each period that affects the income statement.